Pengaruh Return on Equity (ROE) Dan Kurs Terhadap Harga Saham Pada Industri Batubara Sub Industri Produksi Batu Bara Yang Terdaftar Di Bursa Efek Indonesia (BEI) Tahun 2020-2024 - Syahla Nur Fikriyyah; Sintia Anggraeni; Astri Astri; Nafsa Qolbina Istighfari; Alfiana Alfiana (Indo Publishing, 2026)
When making an investment, an investor will consider various factors, both internal and external. This study aims to determine the effect of return on equity (ROE) as an internal factor and exchange rates as an external factor on stock prices in the coal industry and coal production sub-industry listed on the Indonesia Stock Exchange for the period 2020-2024. This study uses a quantitative method with a panel data approach processed through the e-views 13 application through descriptive statistical testing, panel data regression model selection, and classical assumption testing. The test results indicate that the best model that can be used is the fixed effects model (FEM). Partially, ROE has no significant effect on stock prices, while exchange rates have a significant effect on stock prices. The independent variables influence the dependent variable with an influence of 88.66%. These findings indicate that exchange rate fluctuations play a role in influencing stock prices in the coal production sub-industry, while profitability performance as measured by ROE is not always a primary consideration for investors in determining investment decisions in the coal production sub-industry.